2017
DOI: 10.4103/jehp.jehp_72_15
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of health warnings and factors predicting awareness and perceived effectiveness of pictorial health warnings on tobacco products among adults in rural Puducherry, India

Abstract: BACKGROUND:Limited information exists in India about the awareness and perception of the people regarding pictorial health warnings (PHWs) and text warnings on tobacco products, more so from rural areas. Objectives were to report the awareness of these warnings, factors predicting awareness and perceived effectiveness of PHWs, and understanding of their content in a rural population.MATERIALS AND METHODS:A community-based cross-sectional study was conducted in two villages (chosen randomly out of total four) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Importantly, understanding a subject helps shape our thoughts and form judgments about it. Studies have shown that higher perceived impacts were observed among those who understood the pictures and messages conveyed by the PHW, and those who possessed adequate health literacy skills [ 20 , 21 , 22 ]. Hence, these highlights the pivotal role of understanding PHWs towards their perceived effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, understanding a subject helps shape our thoughts and form judgments about it. Studies have shown that higher perceived impacts were observed among those who understood the pictures and messages conveyed by the PHW, and those who possessed adequate health literacy skills [ 20 , 21 , 22 ]. Hence, these highlights the pivotal role of understanding PHWs towards their perceived effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these highlights the pivotal role of understanding PHWs towards their perceived effectiveness. Moreover, studies have shown that the understanding of PHWs is contributed and related to individuals: (i) knowledge, experience, and exposure on the smoking effects, (ii) their belief of the impact shown by the PHW, (iii) having adequate health literacy skills, (iv) the way and image plus language used in presenting the PHW, (v) their interpretation of the PHWs, (vi) the roles of mass media, and (vii) the ability to relate any smoking effects anatomically [ 20 , 21 , 22 , 23 , 24 , 25 ]. The vague understanding of the pictorial contents among most study participants in rural India contributed to the low perceptions of the effectiveness of the PHWs used in the country during the study period [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased taxation and warnings on tobacco packaging have already succeeded in spreading awareness about its harmful effects,[ 9 ] although the awareness of health warnings on tobacco packaging still seems to be low in India even after so many years of implementation of the warnings. [ 10 ] Similarly, increased taxation on SSBs has been found to reduce obesity by decreasing consumption. [ 11 ] Mexico and United Arab Emirates have increased taxes on SSBs to decrease consumption.…”
Section: Introductionmentioning
confidence: 99%
“…India is one among the countries with the highest use of tobacco (T, Thejus and Jayakrishan, 2009). Tobacco packages which are left in public view between users may help in curbing passive smoking as it serves as portable advertisement making nonsmokers aware of deleterious effects of inhaling tobacco smoke (Majumdar, kumar and Selvaraj, 2017).…”
Section: Introductionmentioning
confidence: 99%